Business Development at Inorbit Malls Pvt. Ltd. - Jain, Vaibhav (ATLAS SkillTech University, 2024)
Inorbit Malls Pvt. Ltd., founded in 2004 under the K. Raheja Corp., has been a pioneering force within India's retail industry. Its inception marked a radical departure, exemplified by the launch of the groundbreaking Inorbit Malad Mall in Mumbai. This strategic move ignited a transformative shift in retail by introducing avant-garde shopping destinations that transcended traditional retail norms. Imbued with innovation and a customer-centric ethos, Inorbit Malls expanded across major metropolises, including Hyderabad, Navi Mumbai, Vadodara, and Mumbai's Malad. These multifaceted shopping hubs seamlessly blend retail, lifestyle, gastronomy, and entertainment options. Notably, the company's revenue surged from ₹200 crore in 2004 to a remarkable ₹1,200 crore in 2022. Inorbit Malls set a precedent for modern shopping malls in India, reshaping shopping and leisure paradigms. Malls such as Inorbit offer a harmonious fusion of shopping and entertainment, housing local and global brands, multiple cinemas, gaming zones, and event spaces. This unique amalgamation attracted diverse demographics, significantly catalyzing the expansion of India's retail industry. The company's contemporary online presence underscores its commitment to engaging with stakeholders through platforms like LinkedIn and Instagram.
Project Report on Business Development at Inorbit Malls Pvt. Ltd. (2022-2024) Under the Guidance of Prof. Vinima Gambhir
Keywords: Malls; customer-centric ethos; shopping malls; gaming zones; retail industry; social media